Fintech, Digital Branding, and Customer Engagement to Enhance Gayo Arabica Coffee SMEs' Performance - Deva Djohan; Indra Budiman; Nasib; Mhd Restu Razaq; Mahammad Fathoni (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the influence of financial technology (fintech) and digital branding on the financial performance of Gayo Arabica coffee MSMEs in Central Aceh Regency, with customer engagement as a mediating variable. A quantitative approach was employed, with data collected through questionnaires distributed to 78 MSME actors actively utilizing digital technology in their business operations. Purposive sampling was applied, and data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The findings indicate that both fintech and digital branding have a significant effect on customer engagement and financial performance. Furthermore, customer engagement is proven to be a significant mediating variable in the relationship between fintech and financial performance, as well as between digital branding and financial performance. These results highlight the importance of integrating financial technology and digital branding strategies with customer engagement to optimize business outcomes. This study contributes theoretically to digital entrepreneurship literature and offers practical insights for MSMEs, platform developers, and policymakers particularly regarding financial literacy improvement and brand strengthening. The study is geographically limited, and future research is recommended to conduct comparative studies across sectors and regions.